Knowledge and utilization of sexual and reproductive health services among young males in a slum area in Nigeria: A cross-sectional study - Edith Nnenna Utaka; Adekemi Oluwayemisi Sekoni; Fatai Adesina Badru (Heliyon, 2023)
Background: Globally, young people are faced with sexual and reproductive health challenges such as unintended pregnancies, sexually transmitted infections and unsafe abortions which result from limited knowledge of sexual and reproductive health and poor utilization of the available services. The purpose of this study was to assess the sexual and reproductive health knowledge, pattern of service utilization, and the associated factors among young males in slum communities of Mushin Local Government Area (L.G.A), Lagos State, Nigeria. Methods: The study was conducted among young males, 15–24 years in Mushin Local Government Area, Lagos State, Nigeria. Data was collected using a pre-tested structured questionnaire that consisted of three domains with 57 questions, and was interviewer-administered. Multi-stage sampling technique was used to select 422 participants. Descriptive statistics, bivariate analysis, and binary logistic regression were carried out using SPSS version 20. Results: The mean age of the respondents was 21.01 years ± 2.00, and 73.06% of the respondents had good knowledge of sexual and reproductive health. 52.85% of the respondents had poor knowledge regarding the likely occurrence of pregnancy at mid-menstrual cycle. Nearly two-third (64%) of the respondents have ever visited a health facility for sexual and reproductive health service. Ethnicity(AOR = 2.73), access to the internet(AOR = 1.77) and having ever had sex(AOR = 1.96) were significantly associated with the utilization of the services. Conclusion: Good knowledge of sexual and reproductive health was observed among the respondents, although misconceptions still exist. Service utilization, however, remains low due to some individual and socio-cultural factors. It is therefore important to increase awareness of Sexual and Reproductive Health, and make the services available and affordable to young people for increased uptake.